A Comparative Study for Optimization of Sensitivity and Noise Levels in Race-Track Sensors - Ozkok, Emel; Can, Hava; Inanir, Fedai; Topal, Ugur (SPRINGER, 2017)
In this study, we have designed fluxgate sensors at race-track geometry which were used to measure DC or low-frequency magnetic fields. The type of core material and the number of core layers on the sensitivity and the noise level were specifically examined. We could achieve to get a sensitivity of 440 kV/T and a noise level of 56 pT/ aeHz at 1 Hz in a large dynamical range extending up to 1.5 Oe.
Keywords: Fluxgate magnetometer; Race-track sensor; Sensitivity; Noise level; FLUXGATE; Physics